Penelusuran Informasi Rekam Jejak Alumni Program Studi Informasi, Perpustakaan, dan Kearsipan Universitas Negeri Padang - Sawalinar, Sawalinar; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractÂ This study aims to determine (1) the profile of the graduate, (2) the absorption of graduate in the world of work, (3) the use of knowledge gained by the graduate in the work, (4) the assessment of stakeholders on the ability of graduate. This study uses a descriptive method with a quantitative approach. Data collection uses research instruments. The population in this study was Graduate from the major of Information, Library, and Archives of Padang State University (PS IPK UNP). The sample in this study amounted to 105 graduates who returned the instrument. The results showed, First, the profile of Graduate PS IPK UNP was dominated by female graduates. Most of the graduates are graduates who graduated in 2018. Judging from the length of the study period, the average graduate has a length of the study period of 3 years. Second, the absorption of graduates in the workforce is quite high, with most graduates stating that they are currently working with the time needed to get the job <3 months. Third, the use of knowledge obtained by a graduate at the PS IPK UNP in employment is very high. The science that has a very high level of wear is fieldwork learning, technology mastery skills, and the ability to cooperate in teams. Fourth, the assessment of graduate users (stakeholders) on the ability to graduate in the work world has also been good. The ability of the graduate to be considered good by graduate users (stakeholders) is integrity, expertise based on the fields of science, mastery of information technology, and teamwork.Keywords: Information retrieval, graduate, tracer study